SISTEM INFORMASI PENJUALAN DAN PEMBELIAN PADA CV. FERDI CIKUPA BERBASIS JAVA - Muammar; Ahmad Rifai; Daffa Dhiya Ulhaq; Ibnu Hajar; Karen Azelia Syalom; Samsoni (Journal of Research and Publication Innovation, 2024)
The aim of this research is to design a basic food sales information system at CV. Java-based Ferdi to assist employee performance in processing purchasing and sales data. This system is designed to increase the efficiency and effectiveness of store operations by utilizing information technology. Researchers conducted field studies to understand the shop's business processes in depth, starting from collecting data on goods, ordering to suppliers, to the sales process to customers. Apart from that, researchers also conducted interviews with employees and shop owners to identify system needs. Based on the results of the needs analysis, the researcher designed a system database in the form of interconnected tables to support system functions. The system is designed using the Java programming language with the waterfall method to facilitate system development and maintenance in the future. The main function of the system includes inputting master data such as goods, suppliers and employee data. There is also a module for carrying out sales transactions and ordering goods from suppliers online. Apart from that, there are reports that can be generated by the system such as sales reports, stock of goods, and financial reports for easy business analysis by shop owners. Test results show the system is able to meet business needs and can increase employee productivity.